Ann Brooks’ Postfeminist Studies on Omani Women’s Identity - Rasaf, Najma Imtinan; Basid, Abdul (Journal of Language and Literature, 2024)
This study aims to describe the aspects of influence and identity shaping of female characters in the novel "Sayyidaat Alqomar" by Jokha Alharthi based on Ann Brooks' perspective. This research is oriented towards discussing three aspects, namely postfeminist deconstruction, differences, and women's identity. This type of research is descriptive qualitative research with feminist analysis. Data analysis techniques in this study use the Miles and Huberman method with three stages: data reduction, data presentation, and conclusions. The results of this study are as follows: (1) The influence of postfeminist deconstruction is identified in two aspects. First, gender equality in the relationship between husband and wife and inequality among women. Second, traditional stereotypes that female characters respond as representations of deconstruction with responses to ignore and voice criticism; (2) the differences that affect the identity of female characters are identified, that a woman can own both masculine and feminine sides; and (3) the form of female identity influenced by two factors. First, external factors: destiny and modernization. Second, experience factors: hobbies, work, and trauma. These findings confirm the diversity of Women’s identity in Modernization and pave the way for postfeminist studies towards Omani women.